Prognostic model and immune-infiltrating cell landscape based on differentially expressed autophagy-related genes in TP53-mutated multiple myeloma - Yan-Hua Zheng; Hong-Yuan Shen; Xiang Chen; Juan Feng; Guang-Xun Gao (Archives of Medical Science)
Introduction Autophagy functions as a prosurvival mechanism in multiple myeloma (MM). The objective of this research was to establish an autophagy-related gene (ARG) signature for predicting the survival outcomes of MM patients with TP53 mutations.